Prevalence and Socio-Demographic Correlates of Body Weight Categories Among South African Women of Reproductive Age: A Cross-Sectional Study - Akokuwebe, Monica Ewomazino; Idemudia, Erhabor Sunday (Frontiers in Public Health, 2021)
Background: The shift in disease patterns has been connected with increased body weight burden, becoming a major public health concern in South Africa, as previous studies have assessed overweight or obesity among certain populations. However, little is known about bodyweight burden (underweight, overweight, and obesity) among women aged 15–49 years. Therefore, this study was conducted to identify the prevalence and its associated socio-demographic correlates of bodyweight categories among women of reproductive age in South Africa. Methods: The present study used the South Africa Demographic Health Survey (2016 SADHS) data for 2016. A total of 3,263 women of reproductive age were included in the analysis. Both bivariable and multivariable logistics regressions were performed to determine the prevalence and socio-demographic correlates of bodyweight categories among women in South Africa. Thus, this study used the criteria of the WHO standard body mass index (BMI) cut-offs to classify bodyweight categories. The odds ratios (ORs) with 95% CIs were estimated for potential determinants included in the final model. Results: The overall prevalence of body weight burden was 66.5%, with 4.9% underweight, 27.1% overweight, and 34.5% obese (p < 0.05). The identified factors associated with underweight among women of reproductive age were those from “other” population group [adjusted odds ratio (AOR) 2.65: 95% CI 1.40–5.00], rural residence (AOR 1.23: 95% CI 0.75–2.02), and Northern Cape Province (AOR 1.58: 95% CI 0.65–3.87). For overweight/obese, the main factors were those aged 45–49 years (AOR 10.73: 95% CI 7.41–15.52), tertiary education (AOR 1.41: 95% CI 0.97–2.03), and residing in Eastern Cape (AOR 1.27: 95% CI 0.82–1.99) and KwaZulu-Natal Provinces (AOR 1.20: 95% CI 0.78–1.84). Conclusion: The findings presented in this study indicate the concurrence of underweight and overweight/obese among women aged 15–49 years in South Africa. Despite underweight prevalence being on the decline, yet overweight/obese is increasing over time. The health implication of body weight burden needs rapid and effective interventions, focusing on factors such as rural, education, population group, older age 45–49 years, and Provinces (Northern Cape, Eastern Cape, and KwaZulu-Natal) – the high-risk groups identified herein are of most importance to curb the growing burden among South African women of reproductive age.